Talking Your Self into It: How and When Accounts Shape Motivation for Action - Winchester, Daniel; Green, Kyle D. (Sociological theory, 2019)
Following Mills, several prominent sociologists have encouraged researchers to analyze actors’ motive talk not as data on the subjective desires that move them to pursue particular ends but as post hoc accounts oriented toward justifying actions already undertaken. Combining insights from hermeneutic theories of the self and pragmatist theories of action, we develop a theoretical position that challenges dichotomous assumptions about whether motive accounts reflect either justifications or motivations for action, instead illustrating how they can migrate from one status to the other over time. We develop this perspective through a comparative analysis of actors’ involvements in two quite different careers of social action—religion and mixed martial arts—documenting both how and when justificatory talk about actors’ motives for initiating a course of action at one point in time became formative of their subjective motivations for sustaining these same courses of action at another.